PREVALENCE OF OSTEOMUSCULAR INJURIES AND NUTRITIONAL STATUS OF PROFESSIONAL SOCCER PLAYERS FROM ACRE - de Sousa Júnior, João José Albuquerque; Bezerra de Andrade, Jader; Martins Silva, Romeu Paulo (South American Journal of Basic Education, Technical and Technological, 2022)
As soccer is a sport with high physical demands, tactics and techniques, this brings a large number of musculoskeletal injuries, in addition, it is a modality of higher energy expenditure and, consequently, nutrition must be an important aspect in the athlete’s trajectory. Therefore, the objective was to verify the prevalence of musculoskeletal injuries and nutritional status of professional soccer players in Acre. 39 professional football players from eight clubs in the state of Acre - Brazil, affected by musculoskeletal injuries in the 2019 and 2020 seasons, participated in the study. The athletes had answered a questionnaire regarding the prevalence of injuries and a 24-hour recall on food consumption. As a result, there was a prevalence of 19.37 injuries per 1000 hours of playing, midfielders were the most affected 33.3% of the total, stretching was the most severe type of injury 46.2% of those affected, the anterior thigh with 59% was the most affected, achieving the highest occurrence during the matches. The athletes’ inadequate nutrient intake has been verified, the consumption of carbohydrates with 3.84 g/kg/day and proteins 1.39 g/kg/day, both being below the recommended values as well as the micronutrients vitamin A, B5, C, folic acid, calcium, magnesium, copper, iodine and potassium. In conclusion, the prevalence of injuries in Acreano football is high and the low consumption of macro and micronutrients, may be an indicator of a risky factor for the appearance of injuries.